2016
DOI: 10.1002/jso.24248
|View full text |Cite
|
Sign up to set email alerts
|

What made hyperthermic intraperitoneal chemotherapy an effective curative treatment for peritoneal surface malignancy: A 25‐year experience with 1,125 procedures

Abstract: This study demonstrated that CRS and HIPEC provide long-term survival irrespective of PC origin, and survival improves with experience. J. Surg. Oncol. 2016;113:796-803. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 30 publications
10
79
3
4
Order By: Relevance
“…In 2007, a systematic review of literature reported that observational studies demonstrated an improved OS in patients treated with HIPEC compared with historical controls . Despite the lack of randomized trials, there is an international agreement on the oncological benefits of HIPEC, which is nowadays the main treatment of peritoneal mesothelioma in adults . In the present study, the outcomes of HIPEC for the treatment of peritoneal mesothelioma in children are also encouraging.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In 2007, a systematic review of literature reported that observational studies demonstrated an improved OS in patients treated with HIPEC compared with historical controls . Despite the lack of randomized trials, there is an international agreement on the oncological benefits of HIPEC, which is nowadays the main treatment of peritoneal mesothelioma in adults . In the present study, the outcomes of HIPEC for the treatment of peritoneal mesothelioma in children are also encouraging.…”
Section: Discussionsupporting
confidence: 55%
“…Although CRS and HIPEC are feasible in young patients with peritoneal tumor spread, mortality and morbidity are dramatically high in this series. They are influenced by several factors including the multicentric nature of the series, histologic type of the tumor, local extension, presence of extraabdominal disease, completeness of cytoreduction, and postoperative treatment with chemotherapy and/or abdominal radiotherapy . In the present series, HIPEC was still administered despite CC‐2 resections in two patients and as third‐, fourth‐, and fifth‐line therapy in three, two, and one patients, respectively, although the results are usually dismal in that situation.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The action of 5-fluorouracil is therefore cell cycle specific. These characteristics limit the use of IP 5-fluorouracil to EPIC [19,[76][77][78][79]. 5-fluorouracil is not chemically compatible with other drugs in a mixed solution for infusion or instillation.…”
Section: -Fluorouracilmentioning
confidence: 99%